2016
DOI: 10.1007/978-3-319-32933-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Design and Early Development of a MOOC on “Sustainability in Everyday Life”: Role of the Teachers

Abstract: Universities all over the world have developed Massive Online Open Courses (MOOCs) to attract students and explore new ways of learning. The MOOC "Sustainability in Everyday Life" (SiEL) is currently in its design and early development stage at Chalmers University of Technology. It aims at developing the MOOC participant's capacity to appreciate the complexity of sustainable everyday life by developing skills such as systems thinking and critical reflection on the information flow in public media. This paper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The second MOOC in this study is Sustainability in Everyday Life , also offered by Chalmers University of Technology (Janssen, Nyström Claesson, & Lindqvist, ). The MOOC was on an introductory level and aimed at developing the participant's capacity to grasp the complexities of sustainable development, so as to make better‐informed, more sustainable choices and decisions in everyday life.…”
Section: Study Settingmentioning
confidence: 99%
“…The second MOOC in this study is Sustainability in Everyday Life , also offered by Chalmers University of Technology (Janssen, Nyström Claesson, & Lindqvist, ). The MOOC was on an introductory level and aimed at developing the participant's capacity to grasp the complexities of sustainable development, so as to make better‐informed, more sustainable choices and decisions in everyday life.…”
Section: Study Settingmentioning
confidence: 99%
“…Janssen et al (2016) identified six different roles during the design and early development of their MOOC: owners, teachers, learners, designers, developers, and negotiators. The advice given by Pundak and Dvir (2014) to create an online support center is relevant as a first step to increase the possibility to develop online teaching but also to prepare for and adapt to identity challenges (McNaughton & Billot, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Lecturers' willingness to teach online courses has been examined in many studies (Pundak & Dvir, 2014), but few studies have taken this perspective when studying MOOCs and open courses (Janssen, Nyström Claesson & Lindqvist, 2016;Lang, Zhang, Li & Sun, 2016;Nascimbeni & Burgos, 2016;Ross et al, 2014;Siemens, Gasevic & Dawson, 2015). A recent review of theses and dissertations has been conducted by Bozkurt, Keskin and de Ward (2016) where similar results were found.…”
Section: Introductionmentioning
confidence: 99%
“…Janssen et al (2016) identified six different roles during the design and early development of their MOOC: owners, teachers, learners, designers, developers, and negotiators. The advice given by Pundak and Dvir (2014) to create an online support center is relevant as a first step to increase the possibility to develop online teaching but also to prepare for and adapt to identity challenges (McNaughton & Billot, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Lecturers' willingness to teach online courses has been examined in many studies (Pundak & Dvir, 2014), but few studies have taken this perspective when studying MOOCs and open courses (Janssen, Nyström Claesson & Lindqvist, 2016;Lang, Zhang, Li & Sun, 2016;Nascimbeni & Burgos, 2016;Ross et al, 2014;Siemens, Gasevic & Dawson, 2015). A recent review of theses and dissertations has been conducted by Bozkurt, Keskin and de Ward (2016) where similar results were found.…”
Section: Introductionmentioning
confidence: 99%